Pendampingan Optimalisasi Fungsi Perpustakaan Untuk Menumbuhkan Budaya Baca dan Meningkatkan Kemampuan Literasi Siswa Sekolah Dasar Di Kota Parepare - Wawan Krismanto (Prodi PGSD FIP UNM, 2017)
Based on the results of studies on literacy skills, analysis of the empirical situation and condition of libraries in various elementary schools in Kota Parepare, it can be concluded that the problems faced by the majority of primary schools related to library functions to improve reading culture and literacy skills of students are: 1) governance libraries are still low, 2) the competence of human resources library managers are still low and 3) empowerment of library utilization programs in primary schools to improve reading culture and literacy skills of students who are still low too. So this devotional program provides solutions to overcome the problems of partners in the form of assistance to optimize the function of school libraries. Assistance involves implementers of service programs, lecturers and students in course of Pengelolaan Perpustakaan di SD, principals, teachers, staff and students at 6 partner schools. Stages of mentoring is to rearrange the management of libraries both administration and governance of the room and collections, upgrading the ability of library management and library program development activities to improve reading culture and literacy skills of students. Based on the results of assistance, it can be concluded that the mentoring has succeeded in restoring the function of the library as a center of literacy activities in primary schools. Arrangement of administrative, interior and collections make the library in 6 partner schools an interesting and fun place for student literacy activities. Facilities and programs to improve reading culture and literacy skills of students have also been established and implemented in 6 partner schools.